An Analysis of the Quality of Model Driven Development Solutions Applied to Cyber-Physical Devices - Goncalves, Rafael Figueira; Menolli, André; Dionisio, Gustavo Marcelino (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
The Internet of Things (IoT) is a paradigm that provides an ecosystem for a fast-growing quantity of connected devices, also defined as cyber-physical devices. The creation of Internet of Things solutions is fairly complex, integrating and communicating between sensors, devices, and larger systems. The Model Driven Development (MDD), a software development methodology that allows the generation of software solutions through abstract models, may help to create quality Internet of Things solutions. Thus, this study aims to evaluate the quality of cyber-physical solutions developed from an MDD platform. For this purpose, we performed an quasi-experiment, comparing a well-stable cyber-physical solution with the same solution implemented in an MDD tool. To compare the solutions, we explored several characteristics of ISO/IEC 25010 standard using qualitative and quantitative analysis. The results show the code generated from the MDD tool presented better maintainability and provided the same performance and functional suitability as the original code.